PENGARUH PEMAKAIAN CRYOPROTECTANT BERBEDA TERHADAP SENSORIK DAN KUALITAS KIMIA SURIMI DARI IKAN LELE DUMBO (Clarias gariepinus) - Suryana, Mimy Aulia (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
The aim of this study was to determine the effect of different cryoprotecteur of sensory and quality of surimi from Clarias gariepinus fish. This study used Clarias gariepinus fish and cryoprtectant (sorbitol, sucrose and agar). Sensory test data were statistically analyzed using an analysis of variance (ANOVA) to determine the significant effect of cryoprotectant on the sensory continued the different significance test (LSD), quality data were analyzed descriptively. The results of sensory test color of sorbitol, agar and sucrose ie. 9.67, 9.33 and 7.75, respectively. The Aroma of sorbitol, agar and sucrose ie. 3.50 (fihsy), 3.42 (bit fishy) and 3.33 (bit fishy), respectively. Texture on sorbitol, sucrose and agar ie. 7.50 (strong), 8.08 (strong) and 4.08 (weak), respectively. The results showed that the water content of surimi with the addition of sorbitol, agar and sucrose are 80.77%, 80.55% and 76.92%, respectively. The protein content in surimi with the addition of sorbitol, agar and sucrose are 14.28%, 12.87% and 10.47%, respectively. Whereas, fat content of surimi with the addition of sorbitol, agar and sucrose are 0.89, 0.81% and 0.51%, respectively. The ash content of surimi with the addition of sorbitol, agar and sucrose are 1.94%, 1.48% and 1.28%, respectively.